Asymmetric binding of symmetric guests in a water-soluble cavitand. Issue 5 (3rd June 2018) - Yu, Yang; Zhang, Kang-da; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Rebek, Julius
Abstract: Binding of long aliphatic chains in water-soluble container compounds is driven by the hydrophobic effect: the CH2 groups of the guests are buried from water and solvate the inner aromatic surface of the host. The hydrophobic forces and the CH-π attractions are often sufficient to contort the guests into otherwise unfavorable shapes. Here we show that alkanes, α, ω-diols, α, ω-diacids and their methyl esters assume folded, J-shaped conformations in a water-soluble cavitand. The environment of the guest's ends interconvert rapidly on the NMR timescale through yo-yo like motions. The applications of water-soluble cavitands to reaction processes are discussed in the context of moving vs. fixed guest ends. Abstract :